PENGARUH KEDALAMAN TERHADAP PERKEMBANGAN RUMPUT LAUT KOTONI (Kappaphycus alvarezii) HASIL KULTUR JARINGAN - Runtuboy, Nico; Riyadi, Slamet (Universitas Jambi, 2018)
This research aims to determine the best depth of the development of seaweed seeds produced by tissue culture. The trial was carried out for VI weeks using the same initial weight of seeds which was 75 grams on 3 levels of different water depths: 10 cm, 30 and 50 cm. Parameters observed included plant development, and survival rate. The results of observations of plant development at a depth of 10 cm from the first week to the week to VI the initial weight of 75 g, 115.80 g, 157.40 g, 216.00 g, 303.00 g, 341.00 g and 375.00 g. 30 cm depth initial weight 75 gr, 118,60 gr, 139,80 gr, 199,00 gr, 254 gr 293 gr and 304 gr. 50 cm depth: initial weight 75 gr, 96,6 gr, 122,4 gr, 159 gr, 207 gr, 250 gr and 260,8 gr. Survival rate (SR) at a depth of 10 cm from the first week to the fourth week was 100% and at the fifth and sixth weeks 98% respectively. SR at a depth of 30 cm from the first week to the fourth 100% and the fifth and sixth weeks 96%. And SR at a depth of 50 cm from the first week to the fourth week 100% and at the fifth week 94% and 92%. Based on the results of calculations, the development of plants at a depth of 10 to 30 cm, is relatively the same and gives better results than at a depth of 50 cm. This means that in conducting production activities can be planted at a depth of between 10 to 30 cm.